Evlyia Çelebi in Medina - Gemici, Nurettin. (Evliya Çelebi, 1611?-1682? Seyahatname., 2012)
Evliyā Çelebī, the famous Ottoman traveler of the seventeenth century, visited many countries under the sovereignity of the Ottoman Empire in Europe, Asia and Africa, including the Mecca and Medina. This book offers a critical edition of the section from Evliyā's Travels about Medina. It includes first-hand information on the administrative, historical, cultural, traditional and etymological structure of the city, and on everyday life in Medina during the seventeenth century. Evliyā Çelebī provides the readers with valuable information not only on the city itself, but also on its environs. This book offers a transliteration of the relevant passages on the basis of several Ottoman manuscripts, as well as an English translation made by Robert Dankoff.